MOQUIS AND KASTIILAM hopis, spaniards, and the trauma of history 1680. (UNIV OF ARIZONA PRESS, 2020)
The second in a two-volume series, Moquis and Kastiilam, Volume II, 1680-1781 continues the story of the encounter between the Hopis, who the Spaniards called Moquis, and the Spaniards, who the Hopis called Kastiilam, from the Pueblo Revolt in 1680 through the Spanish expeditions in search of a land route to Alta California until about 1781. By comparing and contrasting Spanish documents with Hopi oral traditions, the editors present a balanced presentation of a shared past. Translations of sixteenth-, seventeenth-, and eighteenth-century documents written by Spanish explorers, colonial officials, and Franciscan missionaries tell the perspectives of the European visitors, and oral traditions recounted by Hopi elders reveal the Indigenous experience.